IMPACT OF PARENT’S LITERACY LEVEL ON THEIR CHILD’S EDUCATION – NEED FOR INTERVENTION - Sudheer, Jonnalagada; K., Suneetha (International Journal of Psychosocial Rehabilitation, 2022)
Education has advanced and pervaded all spheres of existence. It was crucial to a nation’s improvement, even in terms of its economic standing. Parental involvement in their children’s education makes this feasible which requires intervention of their literacy level. Social behaviour and peer pressure of low-literate parents and educational outcomes of students can be influenced by social intervention. This can pave way for a better future of the children. Moreover, illiterate parents confront a number of challenges when attempting to participate in their children’s education. The findings of the study point to a variety of effective intervention strategies for boosting parental involvement, including parent and teacher training programmes, schools practicing community based model to involve parents, and decentralization of educational policies.